Neuroprotective Role of Dietary Supplementation with Omega-3 Fatty Acids in the Presence of Basal Forebrain Cholinergic Neurons Degeneration in Aged Mice - Cutuli, Debora (Int J Mol Sci, 2020)
As major components of neuronal membranes, omega-3 polyunsaturated fatty acids (n-3 PUFA) exhibit a wide range of regulatory functions. Recent human and animal studies indicate that n-3 PUFA may exert beneficial effects on aging processes. Here we analyzed the neuroprotective influence of n-3 PUFA supplementation on behavioral deficits, hippocampal neurogenesis, volume loss, and astrogliosis in aged mice that underwent a selective depletion of basal forebrain cholinergic neurons. Such a lesion represents a valid model to mimic a key component of the cognitive deficits associated with dementia. Aged mice were supplemented with n-3 PUFA or olive oil (as isocaloric control) for 8 weeks and then cholinergically depleted with mu-p75-saporin immunotoxin. Two weeks after lesioning, mice were behaviorally tested to assess anxious, motivational, social, mnesic, and depressive-like behaviors. Subsequently, morphological and biochemical analyses were performed. In lesioned aged mice the n-3 PUFA pre-treatment preserved explorative skills and associative retention memory, enhanced neurogenesis in the dentate gyrus, and reduced volume and VAChT levels loss as well as astrogliosis in hippocampus. The present findings demonstrating that n-3 PUFA supplementation before cholinergic depletion can counteract behavioral deficits and hippocampal neurodegeneration in aged mice advance a low-cost, non-invasive preventive tool to enhance life quality during aging.